Diagnostic utility of single-locus DNA methylation mark in Sotos syndrome developed by nanopore sequencing-based episignature - Takeshi Mizuguchi; Nobuhiko Okamoto; Taiki Hara; Naoto Nishimura; Masamune Sakamoto; Li Fu; Yuri Uchiyama; Naomi Tsuchida; Kohei Hamanaka; Eriko Koshimizu; Atsushi Fujita; Kazuharu Misawa; et al. (Clinical Epigenetics)
Abstract Background In various neurodevelopmental disorders (NDDs), sets of differential methylation marks (referred to as DNA methylation signatures or episignatures) are syndrome-specific and useful in evaluating the pathogenicity of detected genetic variants. These signatures have generally been tested using methylation arrays, requiring additional experimental and evaluation costs. As an alternative, long-read sequencing can simultaneously and accurately evaluate genetic and epigenetic changes. In addition, genome-wide DNA methylation profiling with more complete sets of CpG using long-read sequencing (than methylation arrays) may provide alternative but more comprehensive DNA methylation signatures, which have yet to be adequately investigated. Methods Nine and seven cases of molecularly diagnosed Sotos syndrome and ATR-X syndrome, respectively, were sequenced using nanopore long-read sequencing, together with 22 controls. Genome-wide differential DNA methylation analysis was performed. Among these differential DNA methylation sites, a single-locus DNA methylation mark at part of the NSD1 CpG island (CpGi) was subsequently studied in an additional 22 cases with a NSD1 point mutation or a 5q35 submicroscopic deletion involving NSD1. To investigate the potential utility of a single-locus DNA methylation test at NSD1 CpGi for differential diagnosis, nine cases with NSD1-negative clinically overlapping overgrowth intellectual disability syndromes (OGIDs) were also tested. Results Long-read sequencing enabled the successful extraction of two sets of differential methylation marks unique to each of Sotos syndrome and ATR-X syndrome, referred to as long-read-based DNA methylation signatures (LR-DNAm signatures), as alternatives to reported DNA methylation signatures (obtained by methylation array). Additionally, we found that a part, but not all, of the NSD1 CpGi were hypomethylated compared with the level in controls in both cases harboring NSD1 point mutations and those with a 5q35 submicroscopic deletion. This difference in methylation is specific to Sotos syndrome and lacking in other OGIDs. Conclusions Simultaneous evaluation of genetic and epigenetic alterations using long-read sequencing may improve the discovery of DNA methylation signatures, which may in turn increase the diagnostic yields. As an example of the outcomes of these analyses, we propose that a single-locus DNA methylation test at NSD1 CpGi may streamline the molecular diagnosis of Sotos syndrome, regardless of the type of NSD1 aberration.